THE LIBERTARIAN NONAGGRESSION PRINCIPLE. Issue 2 (29th April 2016) - Zwolinski, Matt
Abstract: Libertarianism is a controversial political theory. But it is often presented as a resting upon a simple, indeed commonsense, moral principle. The libertarian "Nonaggression Principle" (NAP) prohibits aggression against the persons or property of others, and it is on this basis that the libertarian opposition to redistributive taxation, legal paternalism, and perhaps even the state itself is thought to rest. This essay critically examines the NAP and the extent to which it can provide support for libertarian political theory. It identifies two problems with existing libertarian appeals to the NAP. First, insofar as libertarians employ a moralized understanding of aggression, their principle is really about the protection of property rights rather than the prohibition of aggression. Second, the absolutist prohibition on aggression, which libertarians typically endorse and which is necessary to generate strongly libertarian conclusions, is grossly implausible. The essay concludes by setting forth a version of the NAP that does not suffer from these problems. It argues that this more moderate and defensible version of the NAP still has important libertarian implications, but that a full defense of libertarianism cannot rely upon appeals to nonaggression alone.